Rheological and Physical Properties of Gelatin Suspensions Containing Cellulose Nanofibers for Potential Coatings - Osorio-Lira, F; Skurtys-Olivier , F; Andrade-Pizarro, R (SAGE Publications Inc., 2015)
Rheological and physical properties of edible coating formulations containing gelatin, cellulose nanofibers (CNFs), and glycerol are characterized. Measured properties are analyzed in order to optimize edible coating thickness. Results show that coating formulations density increases linearly with gelatin concentration in presence of CNFs. Surface tension decreases with either gelatin or CNF concentration increases. Power law model well described the rheological behavior of edible coating formulations since determination coefficient was high (R2 > 0.98) and standard error was low (SE < 0.0052). Formulations showed pseudoplastic (shear-thinning) flow behavior and no time-dependent features were observed. The flow behavior index was not significantly affected by any factor. Consistency coefficient increases with gelatin concentrations but it decreases with glycerol concentrations. © The Author(s) 2014.